2023
DOI: 10.1002/eat.23980
|View full text |Cite
|
Sign up to set email alerts
|

A multisite comparison using electronic health records and natural language processing to identify the association between suicidality and hospital readmission amongst patients with eating disorders

Charlotte Cliffe,
Marika Cusick,
Sumithra Vellupillai
et al.

Abstract: ObjectivesTo describe and compare the association between suicidality and subsequent readmission for patients hospitalized for eating disorder treatment, within 2 years of discharge, at two large academic medical centers in two different countries.MethodsOver an 8‐year study window from January 2009 to March 2017, we identified all inpatient eating disorder admissions at Weill Cornell Medicine, New York, USA (WCM) and South London and Maudsley Foundation NHS Trust, London, UK (SLaM). To establish each patient'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Within DL applications, alternative AI approaches such as large language models (LLMs) incorporate natural language processing (NLP) to train computers to analyze and understand language and communication. Examples of NLP applications that have application to EDs include the extraction of information from electronic health records (EHRs), analysis of internet activity and social media posts, as well as chatbot development (Beilharz et al, 2021;Benítez-Andrades et al, 2022;Cliffe et al, 2023). A recent systematic review suggested that NLP is in a period of robust development in the medical field, with proportionately high representation from MH fields (Wang et al, 2020).…”
Section: Artificial Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Within DL applications, alternative AI approaches such as large language models (LLMs) incorporate natural language processing (NLP) to train computers to analyze and understand language and communication. Examples of NLP applications that have application to EDs include the extraction of information from electronic health records (EHRs), analysis of internet activity and social media posts, as well as chatbot development (Beilharz et al, 2021;Benítez-Andrades et al, 2022;Cliffe et al, 2023). A recent systematic review suggested that NLP is in a period of robust development in the medical field, with proportionately high representation from MH fields (Wang et al, 2020).…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Examples of studies that have used AI to bolster ED knowledge by extracting information from large data sets have also become increasingly prevalent in the last 2 years. As an example, an international multi-site study that used NLP to explore the association between suicidality and hospital readmission to better predict rates of readmission of patients with EDs found that co-morbid conditions including the presence of a personality disorder were the most predictive risk factor for readmission (Cliffe et al, 2023).…”
Section: Models For Unstructured Datamentioning
confidence: 99%